INTERACTION OF CLASSICAL AND NON-CLASSICAL FORMS IN TRISTAN TZARA’S POETRY - Paladian, Kristiniia (My University, 2015)
The article is devoted to the peculiarities of poetic forms of Tristan Tzara. His verse is rather complex to describe; it changes in evolution without giving the reader a chance to anticipate any rhythmic expectations. The poet’s verses are abundant in various non-classical forms – dolnik, taktovyk, and accent verse. As for classical forms they are used in the form of not fully stressed dolnik. At the same time we must understand that dolnik is just a transitional metric form between syllabic-tonic and tonic. Then the dolnik presence in vers libres seems to be a manifestation of the classical tendency. It gives vers libres a chance to be drawn to ordering and in some cases it restrains some rhythmic shifts in the verse.
Keywords: a classical poem; a non-classical poem; iambus; trochee; dolnik; taktovyk; accent verse